Pol wieku wspomnien - Ginter, Maria (Warszawa : Warszawskie Wydawn. Literackie Muza SA, 1999)
The autobiography of a noted Polish artist and poet, Maria Ginter.
Includes index.
Keywords: Ginter, Maria